IMPACT OF FINANCIAL LITERACY, THE USE OF ACCOUNTING INFORMATION, AND INFORMATION TECHNOLOGY ON BUSINESS PERFORMANCE (MSMEs) IN MATARAM - Erviva Fariantin; Ni Nyoman Yuliati; Nadyatun Munawarah (ShariaBiz International Journal of Economics & Business, 2024)
This study aims to determine how the Effect of Financial Literacy, Use of Accounting Information, and Information Technology on the Performance of Micro, Small and Medium Enterprises (MSMEs) in Mataram City. So that this study consists of 4 (four) independent variables, namely financial literacy (X1), use of accounting information (X2), information technology (X3), and the dependent variable is MSME performance (Y).The type of research conducted in this study is associative.The data collection technique used in this research is a questionnaire.The population in this study was 7,824 MSMEs in the city of Mataram.The sample in this study was taken using the Propionate Stratified Random Sampling technique with a total of 99 MSMEs.The data was obtained by distributing 99 questionnaires via google form to respondents in MSMEs in the city of Mataram.The data analysis techniques used in this research are data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing.The results of this study indicate that financial literacy has no significant effect on the performance of MSMEs. The use of accounting information has a significant effect on the performance of MSMEs. Information technology has a significant effect on the performance of MSMEs.